(untitled) (Sciences & Technology. A, exactes sciences, 2019)
This article presents the design and implementation of a solar adsorption refrigerator using silica gel / water pair for vaccine storage in Sudano Sahelian areas of Cameroon. At first, a complete modeling of the different parts of the solar adsorption machine was carried out, then a calculation program on Matlab is carried out using the climatic conditions (solar radiation, sunshine and temperature) of the city of Maroua. This allowed us to dimension the essential elements of the prototype namely: case, absorber, sideboard, condenser and evaporator. In our program, according to the sunshine and the temperature of the months of April and August 2016 of the city of Maroua in Cameroon, we evaluated the temperatures at the condenser, the evaporator and the cold room. This allowed us to evaluate for its two months the evolution of solar irradiation and the useful energy of desorption in order to calculate the coefficient of thermal performance 〖COP〗 _th, the coefficient of solar performance 〖COP〗 _Sol and solar capture efficiency ɳ of the machine. The results obtained show a satisfactory operation of the solar refrigerator in this city, with thermal performance coefficients having values ​​between 0.0327 and 0.1937 for the month of April against 0.0325 and 0.1576 for the month of April. ’August, and the solar performance coefficients between 0.0226 and 0.151 for the month of April against 0.0216 and 0.108 for the month of August.